What is continuous delivery for Kubernetes? (Manning Publications, 2022)
In this video, Mauricio displays some tools that can help you to speed up your software delivery practices. The tools covered in this video are aimed for developers and architects to design, architect and implement software that can be continuously delivered on top of Kubernetes. Mauricio demonstrates how to implement different release strategies for your services and the trade-offs involved, so you can choose what better fits your needs.